Security and Defence Issues, New Zealand, 1984 (ADA Dataverse, 2018)
Topics in this survey include: ANZUS and New Zealand security; support for variety of forms of defence co-operation; US or New Zealand benefits more from ANZUS; ANZUS and risk of attack of New Zealand; trust in US to come to New Zealand's defence; continue in ANZUS alliance; New Zealand security and US naval forces in Western Pacific and Indian Oceans; visits by US warships with nuclear powered engines; visits by US warships carrying nuclear weapons; visits by any type of US warship; US and New Zealand naval training exercises and ANZUS effectiveness; Western defence alliances and nuclear arms control agreements between US and USSR; strategies for securing Western security. Standard variables include self-placement on left-right spectrum, household size, age, marital status, schooling, occupation of respondent or of main income earner, household income, sex, area. This study is the third of four (SSDA No's 521 to 524) commissioned by the United States Information Service between 1982 and 1985 on New Zealanders' attitudes to defence issues. Similar studies were carried out in Australia at the same time (SSDA No's 525 to 532) which contain some parallel questions.